UPAYA PENINGKATAN PEMBELAJARAN SAINTIFIK DENGAN METODE INVESTIGASI PADA GURU SD BINAAN DI BANDAR LAMPUNG - Hermalia, Hermalia (LPPM STKIP PGRI Bandar Lampung, 2020)
Lack of teacher understanding of techniques and ways to carry out scientific (scientific) approaches in learning, especially teachers in Supervisory Primary Schools. The research objective is to improve the implementation of learning Scientific Approach (Scientific) with the method of Investigation in Elementary Teachers in Bandar Lampung in the Academic Year 2017/2018. The research method uses Classroom Action Research (CAR), with research flow within the 2004 National Education Department, the research cycle starts from planning (planning), organizing, observing and reflecting and following up. Data collection techniques were obtained through observation of activities, mentoring performance, implementation of Scientific Approaches in learning, partnering with partners and colleagues. The results of Cycle I Counseling Performance reached a score of 44 (65%) Good category, Workability 19 (63%), Activity 18 (60%) Active. Cycle II Counseling Performance reached a score of 52 (76%) Good category, 21 (70%), Activity 23 (73%) Active. Cycle III Counseling Performance reached a score of 66 (97%) in the category of Very Good, Workability 26 or (87%), Activity 28 (93%) Active.